NEED FOR TRANSLATION SERVICES IN THE GLOBALIZED WORLD: A PERIPHERY-INFORMED EXPLANATION - Mazlum, Farhad; Shadman, Nazanin; Khademnabi, Mir Mohammad (Sustainable Multilingualism / Darnioji daugiakalbystė, 2024)
The relationship between globalization and translation is one of the new areas of research in Translation Studies. Globalization has led to unstoppable spread of the English language across the globe. Yet, contrary to expectations, not only has the need for translation services not diminished, but it also has increased. This, according to Pym (2003), sounds paradoxical since as the global use of English is on the increase, the need for translation should be waning. In other words, in spite of the fact that the use of English is triumphant and English is already considered the language of the global village, not only has the number of translations not decreased, but the demand for them is increasing. The present study was an attempt to investigate Iranian translators’ views on this paradox. In other words, the study sought the perspectives of translators in the periphery on the paradox to see how the paradox proposed by Pym can be explained from the point of view of Iranian translators. Using snowball sampling, twenty-two translators (all holding an MA or a PhD in Translation Studies) were selected. To collect data, semi-structured interviews were conducted. Interpretive analysis of the data revealed that there are numerous reasons that raise the status and role of translation and translators in the Iranian context, which were categorized under three broad categories, namely the limited target language (English), a preference for Persian over English and ideological issues. As regards the limited English language knowledge, the in-depth interviews showed that the younger generation’s proficiency is mostly confined to oral skills and cannot cover all aspects of the English language. In other cases, technical differences between the two languages were pointed out, which was taken as a barrier for feeling at ease with using English. Additionally, the pervasiveness of English words and phrases in society, and especially technological tools, makes people with little English proficiency feel the need for the translation of these foreign words and phrases. Another broad category concerns the preference of Iranians for Persian over English. Throughout the interviews, even PhD holders pointed out that they were not that much at ease with English, and some mentioned in the interviews that if they had both the English and the Persian version of a text, they would probably prefer the Persian version. Another reason for such preference was shown to be their lack of confidence in their knowledge of English even though they had an advanced level of understanding English texts/talks. The final category dealt with ideological issues at both macro- and micro-level. At the macro-level, some participants referred to the government policy that prioritizes the Persian language over foreign languages in society. At the micro-level, one participant believed that some individuals intentionally use Persian words and phrases to prevent the marginalization of the Persian language.